Research note: Family structure and attitudes toward filial obligations among younger and middle-aged adults - Hämäläinen, Hans; Tanskanen, Antti O.; Kääriäinen, Juha; Danielsbacka, Mirkka (University of Bamberg Press, 2025)
Objective: The study investigates the association between family structures and general attitudes toward adult children's responsibilities to care for older parents.
Background: Despite remarkable changes in family structures in recent decades (e.g., the increasing share of stepfamilies), only a few studies have explored the association between family structures and perceived filial obligations. This study seeks to fill this gap.
Method: Using data from the German Family Panel (pairfam) (N = 8,709) collected from younger and middle-aged Germans, the study examined general attitudes toward adult children's responsibilities to support parents in need. Linear regression models were used to investigate the association between family structure (i.e., respondents without parents and with biological and/or stepparents) and perceived filial obligation.
Results: Respondents with stepparents were less likely to support the idea of filial obligations compared to those without stepparents. In contrast, respondents without living biological parents were more inclined to agree with filial obligations than individuals with living biological parents. Moreover, filial obligations found stronger agreement among males than females and among the younger age cohort compared to older cohorts, regardless of family structure.
Conclusion: The findings highlight how the complexity of the family structures in contemporary society shapes perceived filial obligations.